CURRENT STATUS OF THE DEVELOPMENT OF THE BEEKEEPING INDUSTRY IN OUR REPUBLIC - Jonibek Farmanov; Eshmamatova Aziza Mahmud kizi (Modern American Journals, 2025)
Agriculture has historically been an integral part of Uzbekistan's economic base, with a diverse range of climatic zones suitable for the cultivation of various forms of farming, including crops that support livestock. Among these agricultural practices, beekeeping has emerged as an important sector with the potential to support local economies through honey production and pollination services. This industry not only supports food security and rural livelihoods, but also provides environmental benefits by increasing biodiversity through the pollination of flowering plants [1][2]. Despite its importance, the beekeeping sector in Uzbekistan faces many challenges, including underdeveloped infrastructure, limited access to modern equipment, insufficient knowledge dissemination among beekeepers, and market access restrictions. These challenges hinder the growth potential of the industry, which could otherwise flourish given the country's rich natural resources and favorable conditions for beekeeping.